FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERBANKAN - Ari Sanjaya; Lukman Suryadi (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this research was to test the effect of net profit margin, earnings per share, and firm size on stock prices in companies listed on the financial sector consecutively during the 2019-2021 period. Samples on this research were selected using purposive sampling. This study used data from 156 samples companies. Data processed by using the Econometric Views (EViews) 12 Student Version program. Data processing in this research utilize multiple regression equations. The results of this research indicate that net profit margin and earning per share have a negative significant effect on the stock price, and firm size has a positive significant effect on the stock price.